2014
DOI: 10.1111/bju.12511
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the type of ureteroileal anastomosis on renal function measured by diuretic scintigraphy: long‐term results of a prospective randomized study

Abstract: Objective• To determine the long-term effects of the direct refluxing-type ureteroileal anastomosis technique with those of an antireflux technique on individual renal units, using diuretic scintigraphy in a prospectively randomized study. Patients and Methods• Between 2002 and 2006, a prospective randomized study was conducted on 102 patients undergoing radical cystectomy and urinary diversion.• In every patient, both ureters were randomized to be implanted using a direct refluxing technique or an antireflux,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…We recently provided our long‐term results of a prospective randomised study comparing refluxing and anti‐refluxing techniques of UIA using isotope renography. We found that RFn remains comparable between the techniques .…”
Section: Discussionsupporting
confidence: 55%
“…We recently provided our long‐term results of a prospective randomised study comparing refluxing and anti‐refluxing techniques of UIA using isotope renography. We found that RFn remains comparable between the techniques .…”
Section: Discussionsupporting
confidence: 55%
“…The decreases of GFR are commonly observed following radical cystectomy, and the risk factors include hydronephrosis, pyelonephritis, and ureterovesical stricture [ 19 ]. Harraz et al also reported GFR decreases of ~ 10% after 2 years, with no difference between the refluxing and anti-refluxing type [ 20 ]. To establish an ideal pouch to protect renal function, further investigations are required.…”
Section: Discussionmentioning
confidence: 99%
“…Nonrefluxing techniques have a higher rate of strictures than the refluxing technique, but the latter has harmful effects on renal function because of potential urinary infection [ 27 , 28 ]. However, some researchers believe that these techniques have no significant effect on long-term outcomes [ 29 ]. In this study, our team performed a split-cuff ureteric nipple to avoid urine reflux according to previous experiences.…”
Section: Discussionmentioning
confidence: 99%